Concussion among female athletes in Iceland : exploratory factor analysis on post-concussion symptoms - Eydís Elva Gunnarsdóttir 1996- (2020)
Different factor structures for post-concussion symptoms have been proposed in previous studies. It has been suggested that 1-week post-concussion the symptoms are non-specific, however, when the concussion-injury is less acute the symptoms become more specific. The purpose of this study was to examine the factor structure of the 22-item concussion symptoms list from the SCAT-5. Responses from 166 concussed active and retired female athletes (M = 28.34, SD = 7.38) were collected under three conditions (current symptoms, symptoms after the first concussion, and after their most severe concussion). The results indicated a four-factor structure after the first concussion and their most severe concussion However, factor analysis on current symptoms indicated a six-factor structure. The results are similar to previous studies and indicate that post-concussion symptoms may become more specific in less acute phase of concussion-injury. Keywords: Post-concussion symptoms, female athletes, factor analysis, SCAT-5 Rannsóknir hafa bent á mismunandi gerðir af þáttabyggingum fyrir eftirheilahristingseinkenni. Lagt hefur verið til að viku eftir heilahristing séu einkennin ósértæk, en seinna verði einkennin sértækari. Markmið þessarar rannsóknar var að finna hvort undirliggjandi þættir myndu breytast eftir fyrsta, alvarlegasta og núverandi heilahristings einkenni. Þátttakendur voru 166 íþróttakonur sem höfðu hlotið heilahristing og voru enn að spila eða höfðu áður spilað íþróttir (M = 28.34, SD = 7.38). Niðurstöður benda til fjögurra þátta líkan á einkennum eftir fyrsta og alvarlegasta heilahristinginn, hins vegar bentu þær á sex þátta líkan á núverandi einkennum. Þetta er í samræmi við fyrri niðurstöður og bendir til þess að þegar einkenni eru langvarandi verða þau sértækari. Lykilorð: Eftirheilahristingseinkenni, íþróttakonur, þáttagreining, SCAT-5